Pemilihan Kandidat Campaign Volunteer harisenin.com dengan Metode Profile Matching - Fahrullah Fahrullah; Brigitha Valensia Angela (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2022)
With the opening of the Harisenin Volunteer program, there are also many registrants who want to join as part of harisenin.com. Due to the large number of registrants, volunteer organizers often have difficulty in selecting candidates, because they do not yet use the Decision Support System. To minimize these obstacles, a decision support system is needed that can analyze several candidates according to predetermined criteria. The Profile Matching process is carried out to determine the most suitable candidate recommendations based on 2 main criteria, namely the suitability of tagging friends in the comments column of Calling for Campaign Volunteer posts and the suitability of uploading twibbon and re-uploading Calling for Campaign Volunteer posts. The result of the selection process is the candidate's final score as a recommendation for decision makers to choose the most suitable candidate for harisenin.com.